Utilizing Feed Sequencing to Decrease the Risk of Porcine Epidemic Diarrhea Virus (PEDV) Cross-contamination During Feed Manufacturing - L. L. Schumacher; R. A. Cochrane; J. C. Woodworth; C. R. Stark; C. K. Jones; Rodger G. Main; Jianqiang Zhang; Phillip Charles Gauger; S. S. Dritz; M. D. Tokach (Kansas Agricultural Experiment Station Research Reports, 2015)
Understanding key points of potential cross-contamination during the feed manufacturing process is important to developing efficacious methods to control or prevent transmission of pathogens into swine diets. In this study, an experiment was conducted involving 30 crossbred 10-d-old pigs that were used as a bioassay model for Porcine Epidemic Diarrhea Virus (PEDV) to determine the effects of feed batch sequencing on PEDV cross-contamination and subsequent infectivity. PEDV with a PCR cycle threshold value (Ct) of 11 was uniformly mixed into 4.5 kg of swine diet using a stainless steel bench top mixer validated for mixing efficiency. The inoculated feed was then added to 45 kg of swine diet and mixed using a 4 ft3electric paddle mixer validated for mixing efficiency to form the positive experimental treatment. Feed was discharged, carried into a bucket elevator, and exited through a downspout. Subsequent treatment batches were formed when 50 kg of PEDV-free swine diet was sequenced immediately after the PEDV-inoculated batch without cleaning the equipment to replicate the batching process used in commercial feed mills. The subsequent sequence batches (1-4) mixed, discharged, and sampled similar to the PEDV-positive batch. Feed samples were analyzed for the presence of PEDV using PCR and bioassay. Pigs were then orally challenged with harvested supernatant. Fecal swabs were collected for PEDV PCR testing. At seven days after challenge, all pigs were necropsied. Cecum contents, ileum, and jejunum were collected for PCR, histologic, and immunohistochemistry (IHC) evaluation. Overall, the results indicate that sequencing reduced but did not eliminate the risk of PEDV transmission. All pigs (9/9) challenged with the positive treatment were infected with PEDV with feed that had a Ct mean of 31.7. The discharge for the first sequence had a Ct value of 38.1 and infected pigs were noted in pigs from one of three rooms used to bioassay the feed. The second sequence did not have detectable PEDV RNA by using PCR. Interestingly, feed from the second sequence was infectious as verified by infection in pigs from one of three rooms used for bioassay. This study is the first to demonstrate feed without detectable PEDV RNA can be infective but is similar to other research using tissue homogenates and cell culture as bioassay material. In summary, feed batch sequencing should be considered a risk mitigation strategy that can be incorporated into feed mill biosecurity programs but should not be considered a risk elimination strategy.
Keywords: bioassay; feed; PCR; PEDV; sequencing; swine